Ultrasonic-assisted extraction of phenolic compound from harumanis mango leaves (Mangifera indica) using green Natural Deep Eutectic Solvents (NADESs) - Ahmad Mukhlis Abdul Rahman; Ryan Vitthaya Peron; Amirul Ridzuan Abu Bakar; Muhammad Syaffiq Syazwan Jaafar; Qian, Yee Ang; Mohd Asraf Mohd Zainudin; Nik Muhammad Azhar Nik Daud; Ahmad Anas Nagoor Gunny; Nurul Husna Khairuddin (Penerbit Universiti Kebangsaan Malaysia, 2024)
Harumanis mangoes, known for their taste and nutrition, are a symbol of Perlis, Malaysia. Natural Deep Eutectic Solvents (NADESs) are being studied for eco-friendly extraction methods. There is limited information on green extraction from Harumanis mango leaves, and NADESs have not been used for this purpose. This study aims to evaluate the green extraction of phenolic compounds from Harumanis mango leaves using five NADESs systems, assess the phytochemical composition, and test their antimicrobial potential. These NADESs were prepared by heating and stirring their components until a clear solution was formed. The extraction yields of NADESs were compared with conventional solvents like 100% ethanol, 100% methanol, 50% ethanol, and 50% methanol for extracting phenolic compounds. The chosen NADES was processed with Ultrasonic Assisted Extraction (UAE). The total phenolic content (TPC) in the extracts was measured using a gallic acid standard curve and spectrophotometry. The extract with the highest TPC value from NADES extraction was evaluated for phytochemicals using FTIR and tested for antimicrobial activity with the disc diffusion method. Based on the screening of different NADESs, the highest phenolic content was recorded by lactic acid: glycerol system at 135.74 mg GAE g−1 dw. The lowest TPC value was recorded with sodium acetate: glycerol system, which was 32.76 mg GAE g−1 dw. Among the conventional solvents, the highest TPC value was recorded by 50% ethanol at 133.09 mg GAE g−1 dw, and the lowest TPC value was by 100% ethanol at 67.18 mg GAE g−1 dw. The use of UAE with lactic acid: glycerol NADES system yields the highest TPC value of 142.87 mg GAE g−1 dw. Harumanis extract using NADES-3 had saponins, phenols, glycosides, tannins, and antimicrobial activity on gram-positive and gram-negative bacteria. The results show that NADES effectively extracts phenolic compounds from Harumanis leaves, which have significant therapeutic potential.